2014
DOI: 10.1371/journal.pone.0100751
|View full text |Cite
|
Sign up to set email alerts
|

MiR-133b Regulates the Expression of the Actin Protein TAGLN2 during Oocyte Growth and Maturation: A Potential Target for Infertility Therapy

Abstract: Infertility is an area of increasing in life science research. Although follicular maturation disorders and anovulation are the primary causations of infertility, its molecular mechanism is not well understood. Recent research has shown that microRNAs (miRNAs) might play an important role in the regulation of ovarian follicle development and maturation. In this study, the expression of miRNAs in metaphase I (MI) oocytes treated with or without insulin-like growth factor 1 (IGF-1) was observed by microRNA micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 32 publications
2
45
0
1
Order By: Relevance
“…This outcome may be related to findings in HCC where phosphorylation of TAGLN2 by PFTK1 (an oncogenic serine/threonine protein kinase) inactivates its actin-binding function, abrogating its suppression of cell motility [139] . Fur thermore, in mouse metaphase I oocytes after IGF1 treatment, miRNA133b was upregulated more than 30fold and target TAGLN2 was downregulated, stimulating growth and maturation of the oocytes [140] . These several reports indicate that both the miR133 isomers may target TAGLN2.…”
Section: Cell Factors Deregulated In Cancer By Myomirsmentioning
confidence: 99%
“…This outcome may be related to findings in HCC where phosphorylation of TAGLN2 by PFTK1 (an oncogenic serine/threonine protein kinase) inactivates its actin-binding function, abrogating its suppression of cell motility [139] . Fur thermore, in mouse metaphase I oocytes after IGF1 treatment, miRNA133b was upregulated more than 30fold and target TAGLN2 was downregulated, stimulating growth and maturation of the oocytes [140] . These several reports indicate that both the miR133 isomers may target TAGLN2.…”
Section: Cell Factors Deregulated In Cancer By Myomirsmentioning
confidence: 99%
“…In Májek et al's report, both thrombin and AA group have higher levels of Transgelin-2 but in collagen group no difference was observed between collagen and control groups [54]. Nonetheless, it is taken to be an inflammatory marker [55]. Van Laanen et al in their proteomics study on debris collected from distal protection filter after carotid angioplasty showed that Transgelin-2 in patients with acute inflammation is higher than in patients without acute inflammation [56].…”
Section: Discussionmentioning
confidence: 98%
“…For instance, miR‐152, a member of the miR‐148/152 family, was one of the upregulated miRNAs in the LO group (>2 fold change). In human GV oocytes, miR‐152 was downregulated (>15 fold change) after treatment with IGF‐1 compared with the control (G. Xiao et al, ). In our results, the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that IGF1 and IGF1R are involved in the oocyte meiosis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was assumed that miR‐184 played a role in various steps of oogenesis and early embryonic development in Drosophila (Iovino, Pane, & Gaul, ). It has also been reported to be an abundantly expressed miRNA specific to oocytes but not to the cumulus cells (Assou et al, ; G. Xiao et al, ). miR‐874 inhibits cell proliferation and suppresses tumors through the direct regulation of histone deacetylase 1 (Nohata et al, ).…”
Section: Discussionmentioning
confidence: 99%